Phân hủy toluen trong dung dịch bằng phương pháp siêu âm kết hợp với H2O2 - Hà, Nguyễn Thị; Loan, Lưu Minh; Trung, Nguyễn Quang; Anh, Ngô Vân (VNU Journal of Science: Natural Sciences and Technology; Vol 26 No 3, 2010)
Abstract